First report on rotenoids as neurotoxic principles of seeds from Aeschynomene indica (Leguminosae) - Latorre, Andreia O.; Borghi, Giovana A.; Lopes, Patricia L.; Higa, Kelly C.; Lopes, Lucia M.X. [UNESP]; Maiorka, Paulo C.; Gorniak, Silvana L.; Haraguchi, Mitsue (Medwell Publications, 2011)
Toxic principles from seeds of Aeschynomene indica collected in Brazil were analyzed. Dalpanol, 12 α-hydroxydalpanol and 11-hydroxydalpanol were identified using 1H NMR in A. indica for the first time. 11 -hydroxydalpanol has not been previously reported in the existing literature. Furthermore these rotenoids are likely the toxic principles that cause neurological signs in mice. © Medwell Journals, 2011.
Keywords: 11-hydroxydalpanol; 12 α-hydroxydalpanol; Dalpanol; Mice; Neurotoxicants; Poisonous plants